PERANCANGAN SISTEM E-OFFICE KANTOR WALI NAGARI SUNGAI BULUH SELATAN - Iqbal, Muhammad; Farell, Geovanne (FKDP (Forum Komunikasi Dosen Peneliti), 2021)
The Sungai Buluh Selatan Wali Nagari Office is the Wali Nagari office located in the Batang Anai District, Padang Pariaman Regency, West Sumatra Province. The Wali Nagari office is engaged in population services in making correspondence, such as: DUKCAPIL letters, statement letters, domicile letters, and certificates according to the wishes of the residents, along with the development of the era of the Sungai Buluh Selatan Wali Nagari Office printing letters and conducting population data collection in large scale, thus hindering and complicating the process of recapitating letters and letterhead numbers and collecting data on the population that is still being recapitulated manually. So it makes it difficult for Wali Nagari office employees to find the letterhead number to use because the number of letters is also counted very large. The process of making a letter also still uses Microsoft Word, even though it uses computer technology but it still makes it difficult for employees because they have to type the contents of the letter manually. The annual and monthly operational reporting processes are also still done manually. So that Nagari employees must recap and count the number of incoming and outgoing letters. Therefore, we need an administrative information system for Wali Nagari Sungai Buluh Selatan that can help recap all letter numbers and print administrative documents as well as a complete reporting feature to facilitate the performance of the Nagari office itself.